Farmaceutický význam Allium sativum L. 3. Antibakteriální úcinek proti Helicobacter pylori - Sovová, M; Sova, P; Mrázová, A (Ceska a Slovenska farmacie, 2002)
The paper points out the risk factors which render possible the outbreak of infections due to the bacterium Helicobacter pylori manifesting itself as chronic gastritis. In a great extent it results in peptic and duodenal ulcers and can even lead to the development of adenocarcinoma and lymphoma of the stomach. The paper mentions the efficacy of previous and contemporary therapy. Possible use of garlic in the treatment of these infections is intensively investigated. At present mainly in vitro experiments showing promising results are performed. A minimum of experiments carried out with out-patients produced negative results. As they do not fulfill the parameters of clinical experiments, this question still remains open.
Keywords: Garlic; Helicobacter Infections; Humans; infekce vyvolané Helicobacter pylori; lidé; Helicobacter pylori; rostlinné extrakty; antibakteriální látky; Anti-Bacterial Agents; fytoterapie; česnek; Plant Extracts; Phytotherapy